PENGARUH SEKTE ISLAM SUNNI TERHADAP PERKEMBANGAN POLITIK DI LEBANON - Abdullah Syakir; Sukarma (Qurthuba: The Journal of History and Islamic Civilization, 2021)
Abstract: This article focuses on the history of Islamic sects in Lebanon particularly Sunni Islam and its influence to political development in the country. The thesis was examined by using Gabriel Almond’s Civic Culture Theory. The results of this study concluded that (1) Lebanon is a multi-ethnic and multi-religious country with a confessional system. Namely, the division of power based on a particular religion; (2) The most influential Islamic sects in Lebanon are Sunni, Syi’ah, and Druze; (3) Sunni Islam are divided into several variants. Each variant of this sect competes for influence in Lebanese politics. However, their different paths aimed toward one goal. That is, wanting the establishment of Islamic society according to the Book of Allah and the Sunnah of His Prophet. Keywords: Lebanon, Sunni, Islamic sects, political influence